The Role of the Atypical Kinases ABC1K7 and ABC1K8 in Abscisic Acid Responses - Manara, Anna; DalCorso, Giovanni; Furini, Antonella (Frontiers in Plant Science, 2016)
The ABC1K family of atypical kinases (activity of bc1 complex kinase) is represented in bacteria, archaea, and eukaryotes. In plants they regulate diverse physiological processes in the chloroplasts and mitochondria, but their precise functions are poorly defined. ABC1K7 and ABC1K8 are probably involved in oxidative stress responses, isoprenyl lipid synthesis and distribution of iron within chloroplasts. Because reactive oxygen species take part in abscisic acid (ABA)-mediated processes, we investigated the functions of ABC1K7 and ABC1K8 during germination, stomatal movement, and leaf senescence. Both genes were upregulated by ABA treatment and some ABA-responsive physiological processes were affected in abc1k7 and abc1k8 mutants. Germination was more severely affected by ABA, osmotic stress and salt stress in the single and double mutants; the stomatal aperture was smaller in the mutants under standard growth conditions and was not further reduced by exogenous ABA application; ABA-induced senescence symptoms were more severe in the leaves of the single and double mutants compared to wild type leaves. Taken together, our results suggest that ABC1K7 and ABC1K8 might be involved in the cross-talk between ABA and ROS signaling.